Shikhara (superstructure) of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Formed on multiple miniatures of shikharas arranged in diminishing heights, the shikhara is of the shekhari (multi-spired) variety of the Latina (mono-spired) style of temple architecture. On the front side of the shikhara, there are niches containing deities. The shikhara has been partially rebuilt/renovated.